Late Jurassic Structural Deformation and Late Cenozoic Reactivation of the Southern Junggar Fold-And-Thrust Belt, NW China - Ma, Delong; Yuan, Jianying; Sun, Yanpeng; Wang, Hongbin; He, Dengfa; Wang, Yanjun; Pan, Shuxin; Cui, Jian (Frontiers in Earth Science, 2021)
Because of the influence of the far field effect of the collision between Euro-Asian and India plates during the Late Cenozoic, the Tian Shan orogenic belt underwent intense reactivation, forming the Southern Junggar fold-and-thrust belt (SJ-FTB) to the north and the Kuqa fold-and-thrust belt to the south. Most previous research focuses on the deformation features and mechanisms during the Late Cenozoic. However, little research has been done on deformation features and mechanisms during the Late Jurassic. In this paper, we conducted geometric and kinematic analyses of seismic profiles and outcrop data to reveal the Late Jurassic deformation characteristics in SJ-FTB. Furthermore, we carried out sandbox modeling experiments to reproduce the regional structural evolution since the Early Jurassic. Angular unconformity between the Cretaceous and Jurassic is well preserved in the Qigu anticline belt. This unconformity also exists in the Huoerguosi–Manasi–Tugulu (HMT) anticline belt, which is the second fold belt of the SJ-FTB, indicating that the HMT anticline belt started to become active during the Late Jurassic. The Qigu anticline belt reactivated intensively during the Late Cenozoic, and the displacement was transferred to the HMT anticline belt along the Paleogene Anjihaihe Formation mudstone detachment. Therefore, the present-day SJ-FTB forms because of the two-stage compressional deformation from both the Late Jurassic and Late Cenozoic (ca. 24 Ma).